TECHNOLOGY AND ENTREPRENEURSHIP EDUCATION: A PANACEA FOR JOB CREATION, POVERTY REDUCTION AND SUSTAINABLE ECONOMIC DEVELOPMENT IN NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
Technology and entrepreneurship education serve as catalyst in the sustainable growth of any nation. The paper explored the key concepts of technology, entrepreneurship education, linkages between technology and entrepreneurship education. It investigated technology and entrepreneurship education in Nigeria with its current state and challenges, and policy frameworks and initiatives. Additionally, it examined the technology and entrepreneurship education as a tool for job creation. It also discussed the role in poverty reduction such as enhancing income-generating opportunities, and empowering vulnerable groups (youth, women, rural dwellers). It outlined some contribution to sustainable economic development to include innovation and industrial growth, diversification of the economy, and promoting green and digital entrepreneurship. The paper examined the challenges facing technology and entrepreneurship education in Nigeria such as inadequate funding and infrastructure, skills gap and outdated curriculum, and weak industry–academia collaboration. The findings explained policy recommendations and strategies for improvement. The study concluded that technology enhances entrepreneurship education as it equips youths with skills for self-employment and job creation, fosters innovation and creativity to identify new business opportunities, reduces poverty and unemployment, stimulates economic growth, and builds a mindset of risk-bearing and perseverance for sustainable development. It was recommended among others, that funding of entrepreneurship education and technology should be taken seriously by the federal and state government and that entrepreneurship education should be inculcated into tertiary educational institutions’ curriculum to provide human development.
Keywords: Technology; entrepreneurship education; job creation; poverty reduction; sustainable economic development in Nigeria